Oświęcim ring road development as UNESCO world cultural heritage site buffer zone protection case study - Długosz, Dominika Kinga (Prowadzenie obwodnicy Oświęcimia przykładem ochrony strefy buforowej miejsca kultury, pomnika UNESCO, 2023)
Studying the case of the construction of the ring road of Oświęcim in the vicinity of the former German Nazi concentration and extermination camp Auschwitz-Birkenau (1940–1945), being a UNESCO World Heritage site, the article indicates the need for effective legal protection of an area known as its buffer zone. As current Polish regulations do not provide for such legal protection beyond ad hoc solutions (e.g., provisions included in local zoning plans), the article discusses legal solutions existing in Polish legislation and recommends new ones that can be helpful in ensuring effective protection of designated buffer zones. Listing a site as World Heritage sparks recognition yet entails numerous responsibilities. Since the list includes cultural and natural heritage sites of “outstanding value” to humanity, the prerequisite to preserve their authenticity and integrity is of utmost importance. This also applies to their surroundings. In many cases, the intrusion of such major engineering structures as bridges and highways constructed in the vicinity of a World Heritage site ruins the view and has a negative impact on the cultural landscape developed throughout history. To avoid such cases, in recent years, the UNESCO World Heritage Committee has taken action to promote the mandatory designation of an additional protective, or buffer, zone around the sites to be listed. At the same time, establishing legal protection of such zones in Polish law would make it possible to supervise and control investment activities in such zones.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2023, nr 3 (75), s. 73-79
Keywords: architektura; UNESCO; Memorial and Museum Auschwitz-Birkenau; buffer zone; ring road; Oświęcim; Auschwitz-Birkenau; strefa buforowa; obwodnica